Homocysteine S-methyl transferase regulates sulforaphane concentration in Brassica oleracea var. italica - Gao, Canhong; Lin, Juncheng; Zhao, Liangxia; Xu, Fule; ZHang, Shuiming (The Indian Journal of Genetics and Plant Breeding, 2016)
Homocysteine S-methyl transferase (HMT, EC 2.1.1.10) is a ubiquitous enzyme in angiosperms that plays an important role in sulfur nutrition status. We used over-expression and RNA interference (RNAi) to study the regulatory function of BoHMT1 on sulforaphane concentration in broccoli. Agrobacterium-mediated transforrmation was used to produce 63 putatively transgenic broccoli plants; of these, 51 were positive for the gene construct by PCR selection, and 44 were confirmed by GUS staining. Overexpression of BoHMT1 caused a significant increase in the relative expression level of this gene, and five independent transgenic plants had expression levels >4-fold higher than in the control and they also showed an increase in sulforaphane concentration. Similarly, expression of an RNAi construct decreased the relative expression of BoHMT1, and four independent transgenic lines had expression levels >4-fold lower than in the control, and also showed a reduction in sulforaphane concentration. It is concluded that the BoHMT1 gene regulates sulforaphane concentration in broccoli and that there is a positive relationship between the expression level of the gene and the sulforaphane content.